Effectiveness of a Waste Collection System in Bangkalan Sub-District, Bangkalan District - Aulia, Diva Avriska Mawardah Setya; Meidiana, Christia; Wijayanti, Wawargita Permata; Alfiah, Rindang; Ghosh, Ratan Kumar (Journal of Regional and Rural Studies, 2024)
The discovery of illegal dumping activities in Bangkalan sub-district shows that there is inequality in services provided by the waste collection system. This needs to be reviewed through calculations from an analysis of the effectiveness of the waste collection system in order to assess the performance of waste collection at temporary waste shelter sites in Bangkalan District and improve environmental livability. Therefore, this research aims to evaluate the effectiveness of the waste collection system in Bangkalan Regency through the performance of each temporary waste shelter. The analysis used is the effectiveness of the waste collection system by dividing the output value by the input. The results of the effectiveness analysis will be compared with the Jakstranas document, which states that a temporary waste shelter can be said to be effective if it has an effectiveness value of 100%. Based on calculations, three temporary waste shelter were found in Bangkalan District whose value was below 100%, namely Pangeranan 3R Waste Management which has a percentage value of 15%, recycling house which has a percentage value of 26%, and Martajasah 3R Waste Management, which has a percentage value of 54%. This can be caused by an uneven waste collection system, limited waste infrastructure, limited waste officers, and a lack of public awareness. Apart from that, the existence of illegal dumpings around the temporary waste shelter area is also evidence that the temporary waste shelter is not running effectively.